Analisis Kelayakan Bahan Ajar Cetak dan Digital dalam Implementasi Kurikulum Merdeka di SDN 002/VI Bangko - Muhammad Ali Imron; Egi Agustandi; Shobrina Fitri; Diva Apri Mulya; Rianto (PT. Penerbit Tiga Mutiara, 2026)
The implementation of the Merdeka Curriculum requires teaching materials that align with learning objectives, student characteristics, and school conditions; therefore, the feasibility of printed and digital teaching materials needs to be analyzed. This study aims to compare the feasibility of these formats in fourth-grade learning at SDN 002/VI Bangko based on content, language, presentation, graphics, facilities, and teacher practices. The study employed a descriptive qualitative approach involving one teacher as the informant, while data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, conclusion drawing, and triangulation. The results indicate that printed teaching materials are considered feasible and serve as the primary learning resource because they provide equitable access, are easy to use, can be reused, and do not depend on devices or internet connectivity, while digital materials are feasible as supplementary resources for concept visualization and stimulus variation, although their use remains limited. In conclusion, neither format is absolutely superior, as printed materials provide a foundation for accessibility and learning structure, whereas digital materials enhance visualization and learning variety; therefore, their selection should be flexible, contextual, complementary, and adapted to classroom needs.